Feasibility of an Assessment of the Capital in the Categories of Russian and International Standards of Accounting - Vladimir A. Chernov; Anna V. Borisova (Учёт. Анализ. Аудит)
For the credible and realistic analysis of liquidity of assets, balance, solvency, diagnostics and forecasting of bankruptcy, as well as in anti-crisis management situations, the top necessity is the reliable assessment of assets. The cost of assets which is reflected in the account, credibility of an assessment of net assets define the possibilities of calculations to track liabilities and solvency. The article scrutinises the ways of achievement of a reliable assessment of assets in relation to their real price in case of their possible sale. By means of integration of the provisions RAS and IFRS, and by assessing their similarities and distinctions, the authors consider the possibilities of improvement of quality of information in accounting and the reporting. The article discloses different types of costs which exist according to the Russian and international standards of accounting and the reporting. Net assets are used in the estimation of cost of assets as well as the concepts of fair value. The order of formation of reliable cost at sale of the fixed assets is considered by a method of comparison; upon the purchase of the fixed assets with a payment delay - by a method of discounting; when receiving a loan - on the basis of an effective rate of interest and according to the sum of the actually received money; and in case of determination of cost of stocks - the calculation is according to the net sale price. The offered examples of an assessment of assets and liabilities can be used when choosing the ways of an assessment of the capital in accounting and the reporting, in the financial analysis, in the determination of net assets taking into account a fair assessment, in the diagnostics of bankruptcy and anti- crisis management, when planning and forecasting, when searching for the solutions to the problems of improvement of the quality of information for the economic analysis in the conditions of market uncertainty and variability of the prices. The article might be of interest for students, postgraduates, undergraduates, teachers, scientific and practical workers of the sphere of economy.